Screening of anti-inflammatory activity of 4.5-dihydroisoxazol-5-carboxamide (PAR-2 inhibitors) based on formaldehyde oedema model among white lab rats - Mikhail K. Korsakov; Vladimir N. Fedorov; Nikolay A. Smirnov; Anton A. Shetnev; Olga V. Leonova; Nikita N. Volkhin; Aleksandr I. Andreyev (Belgorod National Research University, 2023)
Introduction: Rheumatoid arthritis (RА) is an immune-inflammatory disease intrinsic to up to 1.0% of the world's population. Standard drugs for RA therapy are basic medications, glucocorticoids and non-steroid anti-inflammatory drugs, which often only ease or hinder the course of disease, not curing the patient completely. Also, on the average 20-50 % of patients are unresponsive to treatment, allergic to the prescribed drugs or find them ineffective. That is why medications with a different mechanism of action are being widely researched, some of them being antagonists of proteinase-activated receptors (PAR-2). Materials and Methods: The inflammatory process was reproduced by injecting a 2% solution of neutral formalin in a volume of 0.1 mL under the aponeurosis of the posterior left foot. A total of 84 white rats were used in the experiment. Diclofenac sodium was administered as a reference drug. Results and Discussion: An experiment on researching the impact of 5 samples of derivatives of 4.5-dihydroisoxazol-5-carboxamide on formalin oedema development among rats showed that the compound R001, compared with other substances studied, differs in the late onset of the therapeutic effect when ingested; the restoration of the foot volume to the initial level occurs only after the introduction of R005, R004 and R002. R005 to a greater extent than other compounds prevents the development of edema and has greater therapeutic efficacy than diclofenac sodium both with intragastric administration and subcutaneous injection. Conclusion: All five compounds in question showed anti-inflammatory activity, with the spectrum not so unequivocal both in qualitative and quantitative values.